KAJIAN DAN PENETAPAN SEBAGAI SITUS CAGAR BUDAYA GUA JEPANG DI TRETES PRIGEN GUNA PELESTARIAN DAN PENCIPTAAN DAYA TARIK WISATA BARU - Suharyono, Edy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
An artificial cave site that is suspected of being a relic of the Japanese army located in the Tretes, Prigen, Pasuruan, East Java Region has long been known by the public, this Cave is located in a resort and famous tourist destination. But the community tends to leave this site unempowered and covered by bushes or buried in the ground, even though if developed this cave will be a very interesting historical tourism attraction. For this reason, it is necessary to conduct a study, assisted by a team of experts from the Archaeological Center to ensure the authenticity and feasibility of the cave as a cultural heritage site and can be developed as one of the tourist attractions in the Tretes region. Keywords : Japanese artificial cave , Tourist attractions, Tourism Development